The Cang-Cang Dance in the Mabang Handak Wedding Tradition Becomes a Performance Dance in Kayuagung City, Ogan Komering Ilir (OKI) Regency, South Sumatra - Kurniaty, Rizki (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
The changing function of the Cang-cang dance, which was originally included in the Mabang Handak wedding tradition, is now widely performed in various art performances and to welcome guests at weddings and invitations to tourism office activities. The problem of this research is